Fluid membrane vesicles in confinement - Osman Kahraman; Norbert Stoop; Martin Michael Müller (New Journal of Physics, 2012)
We numerically study the morphology of fluid membrane vesicles with the prescribed volume and surface area in confinement. For spherical confinement, we observe axisymmetric invaginations that transform into ellipsoidal invaginations when the area of the vesicle is increased, followed by a transition into stomatocyte-like shapes. We provide a detailed analysis of the axisymmetric shapes and investigate the effect of the spontaneous curvature of the membrane as a possible mechanism for shape regulation. We show that the observed morphologies are stable under small geometric deformations of the confinement. The results could help us to understand the role of mechanics in the complex folding patterns of biological membranes.